ANALISIS SISTEM PENDETEKSIAN PLAGIATISME KARYA ILMIAH DI UNIVERSITAS SAHID SURAKARTA - Dwi Retnoningsih; Maslichah Raichatul Janah; Sri Ernawati (JURNAL GAUNG INFORMATIKA, 2016)
Scientific writing will benefit significantly if it is published to the public. Therefore, scientific results can be known and utilized by the community. However, it is also high risky to be imitated by irresponsible parties that this is commonly called plagiarism. One of the subjects must be taken by students at the Sahid Surakarta University is Final Project or Thesis. Sahid Surakarta University does not have a system for detecting plagiarism of scientific writing automatically. The aims of this research is to make an analysis of plagiarism detection system of scientific writing, especially Final Project or Thesis of students Sahid SurakartaUniversity. Analysis of this system used PIECES method which consists of six elements: Performance, Information, Economy, Control, Efficiency and Services. This result of research is an document analysis of detection system in plagiarism of scientific writing at the Sahid Surakarta University.